YKL-40 Gene Expression and Plasma Levels of CD30 are not Affected by Isoflurane or Propofol: Pilot Study - Lak, Shirin; Khorasanizadeh, Shayesteh; Yeganeh, Farshid; Akbari, Mohammad Esmaeil; Haji Molla Hoseini, Mostafa (Novelty in Biomedicine, 2016)
Background: It has been hypothesized that the body's response to anesthesia techniques can increase risk of cancer recurrence and metastatic disease after surgery and also can modulate immune responses. Some acute inflammatory markers have been measured to survey the immunomodulatory effect of anesthesia, but in this research, we studied the plasma level of CD30 and YKL-40 gene expression which can present major changes of the immune system. Materials and Methods: Our study was a controlled before and after study. 34 women with biopsy-proven breast cancer were randomized to receive either propofol general anesthesia (n=17) or standard isoflurane general anesthesia (n=17). There were no significant differences between the two patient groups in age, body weight, and height, length of general anesthesia, operative time and group of surgery. The blood samples were collected in two different sets, before anesthesia and 72-h postoperatively. Soluble CD30 (sCD30) plasma level was measured by ELISA and YKL-40/CHI3L1 gene expression was evaluated by real-time-PCR. Results: The results showed that the anesthetics, propofol and isoflurane, have no effect on the expression of YKL-40. Despite increased in the expression of YKL-40 that was observed in patients receiving isoflurane, this increase was not statistically significant. There was no significant increase or decrease in plasma concentrations of sCD30. Conclusion: YKL-40 and sCD30 are not affected by isoflurane or propofol. So, in immunological perspective, there is no preference in use of isoflurane or propofol in breast cancer patients.